Caribbean Report 11-12-1995 - Ransome, Debbie (anchor); Gordon, Orin (correspondent); Gonsalves, Ralph (interviewee); Werleigh, Claudette (interviewee); Richards, Ken (correspondent); McCormack, Mike (interviewee); Kaufman, Gerald (interviewee); Heaven, Derick (interviewee); Singh, Rickey (interviewee); Cuffy, Victor (interviewee); Fraser, Tony (correspondent) (The British Broadcasting Corporation, 1995)
In this report, France is willing to extradite former Guyanese soldier Gregory Smith to testify at an inquiry into the death of Guyanese activist Dr. Walter Rodney. In Guyana, the inquiry into the Omai Gold Mines cyanide spill concludes with the submission of a report favourable to the Canadian-owned company. Next, the Windward Islands prepares a response to the proposed sale of the banana division of British fruit retail company, Geest. Haiti's Prime Minister Claudette Werleigh plans a secure environment for the December 17th Presidential elections but acknowledges that limited resources could cause problems. Caribbean Report looks at human rights in the Caribbean from Guyana to Cuba. Caribbean Rights Executive Secretary Victor Cuffy highlights what exists and what needs to be done in terms of the region's human rights. In Trinidad, women organizations plan to protest what is being considered a lenient sentence handed down to a 20 year old man who raped an 11 year old girl.
1. Headlines with Debbie Ransome (00:00-00:27)
2. France is willing to assist with the extradition of former Guyanese soldier Gregory Smith (00:28-01:25)
3. The hearing into the Omai Gold Mines cyanide spill has concluded (01:26-03:32)
4. The Windward Islands prepares a statement on the proposed sale of the banana division of Geest (03:33-05:35)
Keywords: Governmental investigations -- Guyana; Extradition -- French Guiana; Water -- Pollution -- Guyana; Pollution -- Environmental aspects -- Guyana; Gold mines and mining -- Guyana; Banana trade -- Windward Islands; Sale of business enterprises; International business enterprises; Elections -- Haiti; Haiti -- Politics and government; Human rights -- Caribbean Area; Prisons -- Guyana; Prisons -- Jamaica; Prison sentences -- Trinidad and Tobago; Punishment -- Trinidad and Tobago; Criminal justice, Administration of -- Trinidad and Tobago; National security -- Haiti; Caribbean Rights (Organization)